Resilience and Post-traumatic Stress Disorder in the Swiss Alpine Rescue Association - Mikutta, Christian; Schmid, Julia J.; Ehlert, Ulrike (Frontiers in Psychiatry, 2022)
Objective: The present study aimed to assess the frequency of trauma exposure, the prevalence of possible post-traumatic stress disorder (PTSD), the extent of resilience, and sense of coherence among personnel of the Swiss alpine rescue association (ARS). Methods: Using a trilingual online survey approach, 465 mountain rescuers of the ARS were surveyed using the Posttraumatic Diagnostic Scale (PDS), the PTSD Checklist 5 (PCL-5), the Resilience Scale 13 and 14 (RS-13/-14), the Perceived Stress Scale 10 (PSS-10), the General Health Questionnaire 12 (GHQ-12), the Pittsburg Sleep Quality Index (PSQI), the Sense of Coherence Scale 13 (SOC-13), and the Berlin Social Support Scales (BSSS). Results: Although the rate of mountain rescuers having witnessed or experienced a traumatic event was high (71%), the prevalence of possible PTSD was low (0.9%). The sample showed high resilience and high sense of coherence. Resilience was positively correlated with work experience. Low perceived stress and high sense of coherence predicted resilience. The severity of PTSD symptoms was mainly predicted by low sense of coherence. Sense of coherence mediated the interaction between resilience and severity of PTSD symptoms. Conclusion: The findings suggest that resilience and sense of coherence are indicative for the low prevalence of possible PTSD among mountain rescuers, and may therefore represent valuable screening and training parameters for mountain rescue personnel.